Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/nar/gkab1044
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of nuclear lamina-associated heterochromatin by HAT1 and the acetylation of newly synthesized histones

Abstract: A central component of the epigenome is the pattern of histone post-translational modifications that play a critical role in the formation of specific chromatin states. Following DNA replication, nascent chromatin is a 1:1 mixture of parental and newly synthesized histones and the transfer of modification patterns from parental histones to new histones is a fundamental step in epigenetic inheritance. Here we report that loss of HAT1, which acetylates lysines 5 and 12 of newly synthesized histone H4 during repl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 101 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…In regions of constitutive heterochromatin, the newly synthesized histones must also acquire methylation on H3 K9, which is likely to be a prerequisite for association with the nuclear lamina(8). The acetylation state of newly synthesized histones may in uence their subsequent methylation as HAT1 and the acetylation of newly synthesized H3 and H4 regulates H3 K9me2/3 in large chromatin domains, termed HADs (HAT1-dependent Accessibility Domains), that show signi cant overlap with LADs (49). Additionally, HDAC2 and HDAC3 are physically associate with the nuclear lamina and may play a role in converting acetylated newly synthesized histones into a form capable of interacting with the nuclear lamina (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…In regions of constitutive heterochromatin, the newly synthesized histones must also acquire methylation on H3 K9, which is likely to be a prerequisite for association with the nuclear lamina(8). The acetylation state of newly synthesized histones may in uence their subsequent methylation as HAT1 and the acetylation of newly synthesized H3 and H4 regulates H3 K9me2/3 in large chromatin domains, termed HADs (HAT1-dependent Accessibility Domains), that show signi cant overlap with LADs (49). Additionally, HDAC2 and HDAC3 are physically associate with the nuclear lamina and may play a role in converting acetylated newly synthesized histones into a form capable of interacting with the nuclear lamina (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to consider that the differences in telomere length we report can also be due to structural alteration ensued by changes in subtelomeric chromatin methylation. An abnormally stable association between telomeres and the nuclear lamina, brought about by an increase in repressive histone modifications such as H3K9me2/3, H3K27me3, and H4K20me2/3 [ 82 ] can lead to stalled replication forks, their collapse, and eventually to telomere shortening. Though quite possible, in order to determine the contribution of these topological features in the recovery of telomeric homeostasis, further studies are required to evaluate the association between the analyzed loci and the nuclear lamina.…”
Section: Discussionmentioning
confidence: 99%
“…An assay for transposase-accessible chromatin using sequencing (ATAC-seq) with MEFs revealed that HAT1 loss results in a reduction in genome accessibility at 1895 sites. These sites, called HAT1-dependent accessibility domains (HADs), are located mostly in the distal intergenic regions with low GC content and low gene enrichment, and they range in size from 0.9 kb to 11 Mb and present characteristics of heterochromatin [ 38 ]. Subsequent experiments demonstrated that HADs localize within lamina-associated domains (LADs; with 86% overlapping).…”
Section: Noncanonical Functions Of Hat1mentioning
confidence: 99%
“…Explaining the mechanisms underlying this HAT1 regulatory function, HAT1 is shown to be a global repressor of H3 K9 methylation and that the HADs correspond to regions where HAT1 regulates the abundance of H3 K9 methylation. The loss of HAT1 results in increases in nuclear size, similar to the effect of decreased lamina expression or mutations that compromise lamina function [ 38 ]. These findings show that HAT1 is a regulator of nuclear structure and integrity.…”
Section: Noncanonical Functions Of Hat1mentioning
confidence: 99%